PENGEMBANGAN PERMAINAN TRADISIONAL CONGKLAK PADA MATERI KONFIGURASI ELEKTRON UNTUK PESERTA DI SMA/MA - Noviyanti Dwi Astuti; Laili Nailul Muna (UIN AR-RANIRY, 2022)
The material of electron configuration is the basis for understanding an atom. Many students have misconceptions about learning this material. The purpose of this research is to develop a traditional game of congklak that can increase students' motivation to learn electron configuration material. The method used in this study uses a 4-D model consisting of four stages, namely: definition, design, development, and dissemination. However, the dissemination stage is not carried out. The assessment of the traditional game of Congklak is carried out by material experts, media experts, reviewers, reviewers, and high school or MA MIPA students. The instruments used to assess quality were a Likert scale questionnaire and a Guttman scale questionnaire. The assessment of media development shows good and ideal results with the following scores: material expert lecturers are 94.00% in the Very Good category, media expert lecturers are 95.50% in the Very Good category, and reviewers (chemistry teachers) get an average score with a percentage of 94.82% in the Very Good category, and the results of student responses to the media showed a percentage of 96.36%. The traditional game of congklak can be used as an alternative to increase students' motivation and enthusiasm for learning electron configuration material in SMA/MA.